TMAI - wartości nominalne wskaźników finansowych czy tempo ich przyrostu? - Węgrzyn, Tomasz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The author compares return rates from portfolios based on nominal value of financial indexes with return rates from portfolios based on growth rates of financial indexes. The first portfolios were named TMAI, the second portfolios were named mTMAI. Researches were conducted on annual financial statements from 1994 to 2004 and quotations of stocks from the Warsaw Stock Exchange between 1995 and 2005. Fifteen stocks with the highest value of TMAI/mTMAI were classified respectively for each portfolio. Each year portfolios were rebuilt on 1st March. It can't be conclusively stated that the portfolios based on mTMAI were better than the portfolios based on TMAI, despite the fact that the compound return rate for the portfolios based on mTMAI were higher by 128% than the compound return rate for the portfolios based on TMAI. It is because during the last three years of research the portfolios based on TMAI two times gave a higher return rate than the portfolios based on mTMAI. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 2, s. 338-347